The Dynamics of Cooperation in Group Lending - A Microfinance Experiment - Peter Werner (Verein für Socialpolitik, 2010)
We conduct a microfinance experiment in which subjects are jointly responsible for credit repayments and decide repeatedly about the effort put into risky investment projects. Although average effort levels are generally high, we find that moral hazard problems still persist among borrowers. Moreover, the path dependency of effort decisions additionally mitigates the insurance effect of joint liability contracts. We compare two conversion mechanisms from joint to individual liability. First, an active selection of the group lending contract does not systematically increase cooperation relative to a reference treatment. Second, conversion based on repayment success tends to have a detrimental impact on effort levels of the remaining joint liability borrowers.
Keywords: O16; I38; C92; 330; Microfinance; group lending; individual lending; social preferences